Association between parental guilt and oral health problems in preschool children: a hierarchical approach - Gomes, Monalisa Cesarino (BioMed Central, 2014)
BACKGROUND: Dental caries and traumatic dental injury (TDI) can play an important role in the emergence of parental guilt, since parents feel responsible for their child’s health. The aim of the present study was to evaluate the influence of oral health problems among preschool children on parental guilt. METHODS: A preschool-based, cross-sectional study was carried out with 832 preschool children between three and five years of age in the city of Campina Grande, Brazil. Parents/caregivers answered the Brazilian version of the Early Childhood Oral Health Impact Scale (B-ECOHIS). The item "parental guilt" was the dependent variable. Questionnaires addressing socio-demographic variables (child’s sex, child’s age, parent’s/caregiver’s age, mother’s schooling, type of preschool and household income), history of toothache and health perceptions (general and oral) were also administered. Clinical exams for dental caries and TDI were performed by three dentists who had undergone a training and calibration exercise (Kappa: 0.85-0.90). Poisson hierarchical regression was used to determine the significance of associations between parental guilt and oral health problems (α = 5%). The multivariate model was carried out on three levels using a hierarchical approach from distal to proximal determinants: 1) socio-demographic aspects; 2) health perceptions; and 3) oral health problems. RESULTS: The frequency of parental guilt was 22.8%. The following variables were significantly associated with parental guilt: parental perception of child’s oral health as poor (PR = 2.010; 95% CI: 1.502-2.688), history of toothache (PR = 2.344; 95% CI: 1.755-3.130), cavitated lesions (PR = 2.002; 95% CI: 1.388-2.887), avulsion/luxation (PR = 2.029; 95% CI: 1.141-3.610) and tooth discoloration (PR = 1.540; 95% CI: 1.169-2.028). CONCLUSION: Based on the present findings, parental guilt increases with the occurrence of oral health problems that require treatment, such as dental caries and TDI of greater severity. Parental perceptions of poor oral health in their children and history of toothache were predictors of greater feelings of parental guilt.